Women and the Reformation in Tudor Ireland - Jefferies, Henry A. (The journal of ecclesiastical history, 2022)
This paper addresses a major historical lacuna by highlighting some of the ways through which women helped to shape Irish responses to the English Reformation in Ireland. It reveals that women were often key to a web of contacts linking English resistance to the Tudors’ reformations to Irish resistance. It affirms that women played a significant role in the Reformation in Tudor Ireland, not least of all in its ultimate failure. Because virtually no Irish women became Protestants in the sixteenth century, though a small number of Irish men was converted, no self-perpetuating indigenous community of Irish Protestants was generated.